the Citizen's Voice Twentieth-Century Politics and Literature - Keren, Michael (University of Calgary Press, 2003)
Michael Keren traces the political lives and messages of some of the twentieth century's greatest literary characters in this insightful and jargon-free book of literary criticism. Hans Castorp (Thomas Mann's The Magic Mountain), Joseph K. (Franz Kafka's The Trial), John the Savage (Aldous Huxley's Brave New World), Winston Smith (George Orwell's 1984), Ralph (William Golding's Lord of the Flies), Merusault (Albert Camus's The Stranger), Ida Ramundo (Elsa Morante's History), and Chauncey Gardiner (Jerzy Kosinski's Being There) participate in ideological, technological, and organizational projects of the twentieth century. Keren observes these infamous characters' behaviours and attitudes while they struggle through world wars, the rise and fall of totalitarianism, the Holocaust, the development of the atomic bomb, de-colonization, the Cold War, and globalization. Here is a refreshing contribution to civil society theory that makes a pioneering effort to cross the boundaries between politics, literature, and culture. A study of the human condition via literature, The Citizen's Voice expounds the key features of a "good citizen" while offering a perfect discussion piece for courses in political theory, politics and literature, and history.